Establishment constraints of an alien and a native conifer in different habitats - Carrillo-Gavilan, Amparo; MARÍA ESPELTA, JOSEP; Vila, Montserrat (BIOLOGICAL INVASIONS, 2012)
Alien plants are subjected to different biotic and environmental barriers that limit their establishment success in the introduced range. Pseudotsuga menziesii (Douglas fir), a native conifer from Northwest America, is considered one of the most invasive forestry conifers in Europe. However, little is known about the ecological filters that constrain plant establishment at early life-cycle stages and differences in habitat invasibility to this species. We conducted field experiments to compare the establishment potential (i.e. post-dispersal seed removal, seed germination, seedling survival and growth) of Douglas fir in beech forests, holm-oak forests and heathlands; and compared it with the taxonomically close native conifer Abies alba (Silver fir). Douglas fir seeds were more removed than Silver fir in holm-oak and in heathlands. In all habitats, seed germination was significantly higher for Douglas fir compared to that of Silver fir and, seedling mortality was extremely high in both species due to soil disturbance by wild boars and drought stress. Douglas fir mortality was only lower than Silver fir in beech forests. However, species did not differ in seedling growth. Overall, the probability of invasion success of Douglas fir decreased along the sequential stages of plant establishment in all habitats. Only high seed germination rates of Douglas fir would predict its high invasive capacity but these advantages are counterbalanced by high seedling mortality. Results showed a mismatch between invasibility and current pattern of Douglas fir invasion in the study area. Therefore, future research focused on seed production and on different components of biotic resistance is recommended to elucidate which processes are favoring its establishment success.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: SPRINGER
Keywords: Abies alba; germination; Invasibility; Pseudotsuga menziesii; Seed removal; seedling survival

Methanolysis of bark suberins: analysis of glycerol and acid monomers - Graça, J; Pereira, Helena (Phytochemical Analysis, 2000)
The depolymerization and subsequent analysis of cork suberins from the outer barks of Pseudotsuga menziesii and Quercus suber was performed using a simpliﬁed methanolysis procedure. The amount of sodium methoxide catalyst was maintained at 20–30 mM and the methanolysis mixture was submitted to trimethylsilyl derivatisation and used directly for gas chromatographic analysis, allowing simultaneous quantiﬁcation of glycerol and long-chain monomers. Response factors for glycerol, ferulic acid and one saturated homologue representing each of the suberinic families (i.e. the 1-alkanols, 1-alkanoic acids, vhydroxyacids and a,v-diacids) were determined. Effective depolymerization of suberin was checked using the infrared specta of the residues after methanolysis. Glycerol is a major constituent of the suberins from P. menziesii (26% of total) and from Q. suber (14%). In both suberins, a,v-diacids are dominant, i.e. 54% of the long-chain monomers in P. menziesii (mostly saturated C16-C22 homologues and the C18 unsaturated diacid), and 53% in Q. suber (mostly the C18 unsaturated diacid and mid-chain oxygenated (epoxide and vic-diol) derivatives). In P. menziesii epoxyacids are absent. The importance of glycerol and a,v-diacids as suberin monomers supports a polymeric structure based on their successive esteriﬁcation.
Keywords: Cork; Glycerol; Methanolysis; monomer composition; Pseudotsuga menziesii; Quercus suber; suberin